An efficient solution for radio frequency measurement - Trần Đình Lâm; Vũ Lê Hà; Đại Xuân Lợi; Lưu Thị Thu Hồng (Journal of Military Science and Technology, 2024)
Radio frequency determination is one of the important parameters in target detection, identification and classification. Some common technical solutions used to determine frequency are spectrum analysis by FFT transformation, direct frequency determination IFM (Instantaneous Frequency Measurement) and signal autocorrelation. This paper proposes a solution to determine radio target frequency applicable to target observation and tracking systems based on the hybrid technique between the effect of stacked filters and real-time spectrum analysis. The IFM-FFT hybrid solution proposed in the paper improves the accuracy of frequency detection and reduces the strictness in the design of stacked filters compared to the IFM solution. At the same time, compared to the pure FFT spectrum analysis solution, the IFM-FFT hybrid solution ensures faster detection time over a wide frequency range.